The use of race quiz media to increase students interest in learning mathematics on the material of whole numbers class VII D SMP Negeri 3 Lawang academic year 2023-2024 - Primandanu, Teguh (International Journal on Teaching and Learning Mathematics, 2023)
With the advancement of science and technology, it is expected to facilitate students in learning mathematics. One method that can be used to learn mathematics is through technology-based media that can be accessed easily by teachers and students. This research is a collaborative classroom action research that aims to increase the interest in learning mathematics of students in class VII D SMP Negeri 3 Lawang in the 2023-2024 school year by using the "Race Quiz" media. The subjects in this study were students of class VII D SMP Negeri 3 Lawang in the academic year 2023-2024 as many as 32 students consisting of 16 male students and 16 female students. The cycle in this Classroom Action Research uses the Kemmis Me Taggart model with the stages of planning, implementation, observation, and observation The instruments used to collect data were observation sheets of learning activities, student response questionnaires for each cycle, and interviews with mathematics teachers. The data obtained was analysed using quantitative descriptive analysis to determine the increase in students' interest in learning mathematics using the "Race Quiz media. Based on pre-cycle data, it shows that students' interest in learning mathematics is 68% so that it can be categorised as sufficient. This class action research was conducted in 2 cycles. The observation results showed an increase in students interest in learning mathematics in the learning process by 6% from 76% in cycle I to 82% in cycle II, so it can be categorised as very high. Therefore, the existence of technology-based learning media is expected to increase students' interest in learning mathematics